A Feasibility Study for Potential of Graphene and Carbon Nanotubes Patch Antenna in Terahertz - Azahari, Wan Azrol Iqbal; Kamarudin, Muhammad Ramlee; Sa'don, Siti Nor Hafizah (Evolution in Electrical and Electronic Engineering, 2021)
Today’s Eureka moments are in wireless communication technology. There has been a significant increase in the number of new use cases for which 5G is inadequate. 6G will allow a highly intelligent, reliable, scalable, and secure terrestrial wireless network. New antenna structures for wireless communication systems have been designed as a result of increased attenuation for high frequency. The researchers offer a 6G architecture idea as well as antenna specs in the Terahertz wavelength range. According to researchers, such an antenna may be used for a variety of applications, including communications. The major goal of this study is to develop graphene and carbon nanotube (CNT) antennas for a variety of Terahertz bands, as well as to examine the antennas’ performance in those bands. The primary objective of the task is to do research and study the proper formula and theory in order to acquire accurate parameters utilising CST Studio, which offers an interface for accessing data. At frequencies ranging from 100 GHz to 500 GHz, a novel design will be developed and tested. It will be based on graphene and carbon nanotube (CNT) materials for comparison of results, and the antenna size will be decreased to minimise meshcells, which will make troubleshooting simpler in a short period of time. Both materials’ results suggested that they were suitable for use at terahertz frequencies. This is just one of several steps in the development of graphene and carbon Nanotube antennas. Although the various antennas are not completely developed, they all have potential. There is a market for further research and manufacture of these antennas in the near future.